A Knowledge Behavioral and Intelligence Management in Fostering Entrepreneurship for Modern Industries - Faiz Alfazzi (Bright Institute, 2022)
The major goal of this work is to investigate the relation between management strategic intelligence (SI), organizational Development (OD), and Entrepreneurial Behavior (EB) in government agencies in developing nations. In a larger sense, while knowledge and experience have separate effects on an entrepreneur's decision-making process and behavior, there have been no proven research on how similar characteristics affected decisions and behaviors during the entrepreneurial transition. The influence of knowledge and experience was investigated in this study. The C-square test indicated that knowledge and experience are statistically relevant for entrepreneurs, demonstrating vision, independence, achievement, and responsiveness, using the smart approach for data collecting and analysis. This research focused on business decisions have been made. The indirect impact demonstrates that supervisors combination of knowledge management, emotional intelligence, and entrepreneurial abilities has a statistically favorable influence on organizational innovation. This technique contributes to the scientific as well as economic consequences. Scientific impact, in the form of new knowledge that reinforces the value of executives as innovation catalysts; and a new socio-economic management tool to improve the socio-economic impact, human systematic innovation helix, knowledge management skills, socio-emotional skills, and business skills of executives. Companies. This effort has increased understanding of the influence of delayed or postponed action on your business growth decisions.